Plasticity in ascending long propriospinal and descending supraspinal pathways in chronic cervical spinal cord injured rats - Côté, Marie-Pascale; Detloff, Megan R.; Wade, Rodel Jr; Lemay, Michel A.; Houlé, John D. (Frontiers in Physiology, 2012)
The high clinical relevance of models of incomplete cervical spinal cord injury (SCI) creates a need to address the spontaneous neuroplasticity that underlies changes in functional activity that occur over time after SCI. There is accumulating evidence supporting long projecting propriospinal neurons as suitable targets for therapeutic intervention after SCI, but focus has remained primarily oriented toward study of descending pathways. Long ascending axons from propriospinal neurons at lower thoracic and lumbar levels that form inter enlargement pathways are involved in forelimb-hindlimb coordination during locomotion and are capable of modulating cervical motor output. Magnetic stimulation was used as a non-invasive investigational tool to assess transmission in long ascending propriospinal pathways to investigate how a unilateral cervical spinal contusion that does not directly damage this pathway might influence spinal cord plasticity. Our results show that transmission is facilitated in this pathway on the ipsilesional side as early as 1 week post-SCI. We also probed for descending magnetic motor evoked potentials and found them absent or greatly reduced on the ipsilesional side as expected. H-reflex recorded from the forelimb triceps brachii was bilaterally impaired although Hmax/Mmax was increased only on the ipsilesional side. Behaviorally, stepping recovered, but there were deficits in forelimb-hindlimb coordination as detected by BBB and CatWalk measures. In summary, results suggest that uninjured, initially latent pathways mediate recovery pointing towards functional reorganization of spinal pathways rather than axonal sprouting as a mechanism for spontaneous recovery after SCI.